Penerapan Akad Rahn Pada Pegadaian Syariah Perspektif Ekonomi Islam - Ekarina Katmas; Mindo Mursalina jen (At-Thariqah: Jurnal Ekonomi, 2021)
The results obtained show that (1) the application of the rahn contract at the klademak sharia pawnshop followed by mu'nah fees (guarding and maintenance) as a source of pegadaian syariah income by providing services on customer guarantee goods (2) the implementation of the rahn contract at the klademak pegadaian syariahIn general, it is in accordance with the MUI DSN Fatwa No. 25/DSN-MUI/III of 2002 and DSN MUI Fatwa No. 92/DSN-MUI/IV of 2014, this can be seen from the general provisions adapted to the Fatwa of DSN MUI No. 25/DSN-MUI/III of 2002 and the provisions on collateral, debt provisions, contract provisions, murtahin income provisions and contract settlement provisions which are adapted to the DSN MUI Fatwa No. 92/DSN-MUI/IV 2014. The implication of this research theoretically can be seen the operational implementation of the rahn contract at Pegadaian Syariah Klademak Branch, Sorong City, which is in accordance with the MUI DNS fatwa no. 25/DSN-MUI/III of 2002 and DSN MUI Fatwa No. 92/DSN-MUI/IV of 2014. Practically this research can be used as a scientific reference and can have positive implications for certain parties.